The causes of cellulite - Leszek Zakrzewski; Agnieszka Michalska; Andrzej Śliwczyński; Patrycja Szczepańska (Polish Pharmaceutical Society, 2021)
Cellulite as an aesthetic problem has been known for many years. It is a physiological phenomenon found in women. There are many concomitant factors that can trigger, persist, or exacerbate it. Of particular importance among these factors is the architecture of connective tissue, the action of estrogen, micronucular lesions and genetic and hormonal characteristics. The article presents theories about the factors that affect the occurrence of cellulite. It was taken into account changes in the cross-section of connective tissue and in the flow of blood vessels ,the effect of chronic adipose tissue inflammation, as well as genetic or hormonal conditions on the occurrence of cellulite. Particular attention was paid to the inflow of changes in the subcutaneous cross-section of connective tissue to the occurrence of cellulite. Nürnberger and Müller in 1978 were the first to notice significant differences between men and women in the structure of subcutaneous fat. Considered the aging aspect of skin cells, which was studied by various scientists. Quaglino found that the diameter of collagen fibers is the largest between the ages of 10 and 29, and begins to decline after the age of 30, reaching minimum values at the age of 60. In addition, attention was paid to the relationship between the occurrence of vascular lesions and the localization of cellulite. In 1999, Gruber and Huber pointed out that ovarian hormones have many functions and are responsible for differences between men and women in the incidence of certain diseases. The distribution of subcutaneous tissue in the human body is genetically conditioned, and its thickness depends on the type of diet, state of health, influence of hormones. Cellulite usually appears in areas where adipose tissue is altered under the influence of estrogen. It was found that excessive weight increases the risk of cellulite. The most commonly used classification for cellulite degree characteristics was proposed by Nürnberger & Müller in 1978 and is still known today.